Literasi Mitigasi Bencana Covid-19 - Syahrial Ayub; Chairunisyah Sahidu; Joni Rokhmat; Muhammad Zuhdi; Muhammad Taufik; Gusti Afifah (Kappa Journal, 2021)
Corona Virus (Covid-19) is a new type of virus that is transmitted from human to human through the mouth, nose and eyes. This virus attacks the respiratory system which can lead to death. This virus makes the world restless, because it is a new type of virus, so many parties do not know and do not understand how to deal with it. One thing that can be done to reduce the risk of being exposed to Covid-19 is to be disciplined in implementing health protocols. Health protocols are only limited to efforts to protect themselves from patient droplets, but do not provide full protection. SMAN 2 Mataram is one of the schools with 1685 students and 36 study groups. The large number of students and groups makes SMAN 2 Mataram vulnerable to Covid-19 transmission. There is no other choice, except to prepare students as early as possible to have awareness in mitigating the Covid-19 disaster at school. One of the efforts made is literacy education for the Covid-19 disaster mitigation. Implementation of Covid-19 disaster mitigation literacy education through Covid-19 disaster mitigation learning with the Covid-19 disaster mitigation literacy learning model. The research was conducted in class X MIPA1 SMAN 2 Mataram which resulted in students' awareness of the Covid-19 disaster mitigation in the form of inadequate knowledge and application of health protocols, even though they received sufficient information and knowledge about Covid-19. The role of the school in the form of a task force must be optimized to control students in implementing health protocols so that students feel safe when doing activities at school.